Crystallization and preliminary X-ray crystallographic analysis of a helicase-like domain from a tomato mosaic virus replication protein - Xiang, Hongyu (International Union of Crystallography, 2011)
Tomato mosaic virus belongs to the genus Tobamovirus in the alphavirus-like superfamily of positive-strand RNA viruses. The alphavirus-like superfamily includes many plant and animal viruses of agronomical and clinical importance. These viruses encode replication-associated proteins that contain a putative superfamily 1 helicase domain. No three-dimensional structures for this domain have been determined to date. Here, the crystallization and preliminary X-ray diffraction analysis of the 130K helicase domain are reported. Diffraction data were collected and processed to 2.05 and 1.75 Å resolution from native and selenomethionine-labelled crystals, respectively. The crystals belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 85.8, b = 128.3, c = 40.7 Å.